THE EFFECT OF NATURAL RUBBER LATEX ON CUTBACK ASPHALT CHARACTERISTIC FOR PATCHING - Hermadi, Madi (Jurnal Jalan Jembatan, 2018)
There are some problem in applying cold mix cutback asphalt, among others is the low evaporating rate or unpropper evaporating of the solvent. This case makes the initiate mixture has a long curing time and a low stability. In order to ever come that problem, we would like a perform the effect of natural rubber latex on characteristic of cold mix cutback asphalt and applying it in patching. The use of a few percent of natural rubber latex in cold mix could increase the viscosity, because of polymerization process in low temperature, of asphalt cut back binder rapidly, even the solvent has low evaporating rate or unpropper evaporated. Hence, the cold mix has a short curing time and a high stability. Beside that the rubber could increase the quality of residual binder in mixture such as elasticity.